Fiscal Competition and the Composition of Public Expenditure: An Empirical Study - Hannes Winner (Contemporary Economics)
This paper investigates whether fiscal competition affects the structure of public spending, where theory predicts a shift from residential public goods to industrial public goods. We propose an empirical model that specifically accounts for the strategic nature and endogeneity of fiscal competition. Using data for 18 OECD countries and a time period with unprecedented tax competition (1980 to 2000), we find a significant impact of fiscal competition on the composition of public expenditure. This finding is in line with theoretical research, particularly that of Keen and Marchand (1997).